Sosialisasi Hukum tentang Pencegahan Perundungan (Cyberbulliying) di Media Sosial dalam Pengaturan UU ITE terhadap Siswa MAN Filial 1 Kubu Raya - Chermansah Chermansah; Riki Ansera; Sohibuddin Sohibuddin; Syarif Abdullah; Ismail Ismail; Rama Rama (Jurnal Informasi Pengabdian Masyarakat, 2026)
The rapid development of internet-based information technology has brought various impacts on society, including the emergence of digital crimes such as cyberbullying. Cyberbullying refers to acts of intimidation, harassment, or humiliation carried out through digital media, which can have serious psychological consequences, particularly for adolescents whose emotional development is still vulnerable. This community service program was conducted at MAN Filial 1 Kubu Raya with the aim of improving students’ understanding of the legal aspects of cyberbullying and the provisions regulated under the Indonesian Electronic Information and Transactions Law (ITE Law). The main issues identified were the low level of students’ legal literacy regarding digital media use and the perception that cyberbullying is not a significant issue requiring serious attention. The program employed an interactive legal socialization approach through presentations, discussions, and question-and-answer sessions. Students were also educated about the legal consequences of intimidation and bullying conducted in digital spaces. The results indicated an improvement in students’ understanding of legal boundaries in social media use, the legal risks associated with cyberbullying, and the importance of maintaining ethics in digital communication. Therefore, legal awareness programs have proven effective in enhancing students’ legal knowledge and encouraging the wise, responsible, and lawful use of digital technology in accordance with applicable regulations.